A eficácia da convenção sobre os direitos das pessoas com deficiência no Brasil - Santos, Maria Lucia Ribeiro dos (2014)
The present dissertation has as purpose to investigate the problem of the effectiveness of the protection on the rights of persons with disabilities, in light of the Constitution of 1988. Thus, the study begins with a brief history about people with disabilities, seeking about the concept and terminology that were building over the centuries. The research is centered on the question of the implementation of the treaties and conventions on human rights in Brazil, notably the Convention on the rights of persons with disabilities. This way, it will analyze the respect of receipt of international treaties and conventions dealing with human rights on the basis of the legal parental rights. For both, is used as a reference the earlier and the later the validity of Constitutional Amendment no. 45, December 30, 2004. In this context, we will examine the issue of the implementation of this Convention, from, in particular, the introduction of the new wording of paragraph 3, Article 5 of the Federal Constitution of Brazil, thereby strengthening the prism of constitutional hierarchy. On this occasion, there will be a holding on the various doctrinal positions relating to admission and success of international baccalaureate in Brazilian law. Finally, ventilate will be the fulfillment of the applicability conferred by Brazilian justice regarding the filing of actions that require the protection of the rights of people with disabilities; in this context, the object is examined on the prospect of contemplation of effectiveness with views into the materialization of the progress of the constitutionalism Brazilian directed to the achievement of an aspirated Humanistic nation and Constitutional Law.